Counseling on homes and healthy lifestyles for Baduta Mothers in the stunting locus area - Ernawati, Kholis; Yusnita, Yusnita; Jannah, Fathul; Utami, Melsya Halim; Rahmatia, Annisa; Akhir, Chorunnisa Yaumal; Rizki, Fitria (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Home and the residential environment are one of the risk factors for stunting. The level of knowledge determines residents' behavior, and knowledge is influenced by the exposure to information that a person receives. The purpose of community service activities is counseling about healthy homes and healthy behavior to Baduta mothers (children under two years) in the stunting locus, Langensari village, Pandeglang district. Extension activities were carried out on September 20, 2019, in Langensari village, Saketi District, Pandeglang Regency. Before the activity was carried out, the team carried out advocacy and licensing at the Saketi District Health Center and the Langensari Village Head. The method used in this activity is advocacy and socialization of activities and activities using extension media using posters and brochures. The target of the counseling is the Baduta mother. Participants will be assessed whether there is increased knowledge about healthy homes and healthy behavior before and after counseling (pre-post-test). The result of the educational activity was that the extension participants consisted of 39 Baduta mothers. The difference in the mean score of the pre-post-test was 0.821, and the extension activities could increase the participants' knowledge before and after counseling (p = 0.018).